Electrode composite material
Patent Information
- Application Number
- JP2022025175
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-02-22
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2042-02-22
AI Technical Summary
【0008】 本開示は、全固体電池の初期抵抗と放電容量と抵抗増加率のバランスに優れる電極合材を提供することができる。
Smart Images

Figure 0007639732000002 
Figure 0007639732000003 
Figure 0007639732000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrode mix. [Background technology]
[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras, and mobile phones, the development of batteries to be used as power sources for these devices has become important. In the automobile industry, too, development of high-output, high-capacity batteries for electric vehicles or hybrid vehicles is underway.
[0003] Patent Document 1 discloses a positive electrode for an all-solid-state battery, in which the ratio (external / whole) of the specific surface area of the external surface to the total specific surface area including pores is less than 0.5, and which contains a conductive material having a conductivity of 1 S / cm or more. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-258080 A Summary of the Invention [Problem to be solved by the invention]
[0005] In an electrode mixture for an all-solid-state battery, contact between a conductive material and a solid electrolyte may cause decomposition of the solid electrolyte, resulting in an increase in resistance and a decrease in durability of the all-solid-state battery.
[0006] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide an electrode mixture having an excellent balance between the initial resistance, discharge capacity, and resistance increase rate of an all-solid-state battery. [Means for solving the problem]
[0007] The electrode mixture of the present disclosure is an electrode mixture for an all-solid-state battery, The battery includes an active material, a solid electrolyte, and a conductive material, In the Raman spectrum measurement of the conductive material, -1 Intensity of the peak at 1350 cm -1 The intensity ratio D / G of the peak intensity D of the conductive material is multiplied by the content W (mass%) of the conductive material to obtain the specific surface area Si (m 2 / g) and multiplying the result by 100, the conductive loading parameter of the conductive material is greater than 0.16 and less than 2.29; The contact interface length (pixel) between the conductive material and the solid electrolyte is greater than 480 and less than 7300. Effect of the Invention
[0008] The present disclosure can provide an electrode mixture that has an excellent balance between the initial resistance, discharge capacity, and resistance increase rate of an all-solid-state battery. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a diagram showing the results of Raman spectrum measurement of the conductive material used in Example 1. [Diagram 2] FIG. 2 is a diagram showing the measurement results of the sulfur S2p spectrum of the solid electrolyte used in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the embodiments of the present disclosure will be described. Note that matters other than those specifically mentioned in this specification and necessary for implementing the present disclosure (for example, the general configuration and manufacturing process of the electrode mixture that do not characterize the present disclosure) can be understood as design matters of a person skilled in the art based on the prior art in the field. The present disclosure can be implemented based on the contents disclosed in this specification and the technical common sense in the field. In this specification, the use of "to" indicating a numerical range means that the numerical values before and after it are included as the lower limit and upper limit. Furthermore, any combination of upper and lower limits in a numerical range can be used.
[0011] The electrode mixture of the present disclosure is an electrode mixture for an all-solid-state battery, The battery includes an active material, a solid electrolyte, and a conductive material, In the Raman spectrum measurement of the conductive material, -1 Intensity of the peak at 1350 cm -1 The intensity ratio D / G of the peak intensity D of the conductive material is multiplied by the content W (mass%) of the conductive material to obtain the specific surface area Si (m 2 / g) and multiplying the result by 100, the conductive loading parameter of the conductive material is greater than 0.16 and less than 2.29; The contact interface length (pixel) between the conductive material and the solid electrolyte is greater than 480 and less than 7300.
[0012] The conductive material forms an electronic path in the solid electrolyte, accelerating the decomposition reaction of the solid electrolyte. Therefore, in the electrode mixture of the present disclosure, the decomposition reaction of the solid electrolyte is controlled by controlling the conductive load of the conductive material on the solid electrolyte.
[0013] [Electrode composite material] The electrode mixture of the present disclosure includes an active material, a solid electrolyte, and a conductive material. The electrode mixture of the present disclosure may be a positive electrode mixture used in a positive electrode layer, or a negative electrode mixture used in a negative electrode layer. The active material may be a positive electrode active material or a negative electrode active material described below. As the solid electrolyte, the same ones as those exemplified in the solid electrolyte layer described later can be exemplified. The solid electrolyte may have a PS4 skeleton of 70% or more. The specific surface area of the solid electrolyte is 5 to 200 m 2 / g. The conductive material may be the same as those exemplified in the positive electrode layer described later. The conductive material may be used alone or in combination of two or more. The specific surface area of the conductive material is 5 to 2000 m 2 / g. The shape of the conductive material is not particularly limited, and may be fibrous, spherical (particulate), or the like. The mass ratio (mass %) of the active material to the solid electrolyte may be active material:solid electrolyte=65:35 to 85:15.
[0014] [Conductive load parameters] In the electrode mixture of the present disclosure, the conductive material has a conductive load parameter that is greater than 0.16 and less than 2.29, and may be 0.19 to 1.15. If the conductive load parameter is 2.29 or more, the initial resistance is high, the solid electrolyte is easily decomposed, and the durability of the all-solid-state battery is reduced. If the conductive load parameter is 0.16 or less, the desired conductivity cannot be obtained. The conductive loading parameter is the Raman spectrum of the conductive material at 1600 cm -1 Intensity of the peak at 1350 cm -1 The intensity ratio D / G of the peak intensity D of the conductive material is multiplied by the conductive material content W (mass%) to obtain the specific surface area Si (m 2 / g) and multiplying by 100. The conductive material content is the content in the electrode mixture. That is, the conductive load parameter can be calculated from the following formula (1). Equation (1): Conductive load parameter = (D / G) × W÷Si × 100 When two or more conductive materials are used, the conductive load parameter of each conductive material is calculated, and the total value of these should fall within the above range. The conductive material may have a D / G ratio of 0.01 to 1.
[0015] [Contact interface length] In the electrode mixture of the present disclosure, the contact interface length (pixels) between the conductive material and the solid electrolyte may be greater than 480 and less than 7,300, and may be 1,800 to 6,700. The length of the contact interface between the conductive material and the solid electrolyte can be controlled by the timing of adding the conductive material and the solid electrolyte, the kneading time, the type of solvent, and the like when preparing the slurry for the electrode mixture. The contact interface length [px] between the conductive material and the solid electrolyte is calculated as follows: Images of carbon (C) as a conductive material and backscattered electron images are obtained by SEM-EDX, and four-value processing is performed using image analysis software (e.g., ImageJ). The ratio of the solid electrolyte components to the carbon components is calculated, and the length of the part where the solid electrolyte components and the carbon components are in contact can be calculated as the contact interface length.
[0016] [Strength ratio B / A] When the electrode mixture of the present disclosure is used in an all-solid-state battery, the intensity ratio B / A of the peak intensity B around 162 eV to the peak intensity A around 159 to 160 eV in the sulfur S2p spectrum of the solid electrolyte obtained by XPS after initial charge and discharge may be greater than 0.39 and less than 0.85, or may be 0.45 to 0.61. This allows the all-solid-state battery to have high durability.
[0017] [All-solid battery] The electrode mixture of the present disclosure is an electrode mixture for an all-solid-state battery. The all-solid-state battery of the present disclosure may include a positive electrode, a solid electrolyte layer, and a negative electrode.
[0018] [Positive electrode] The positive electrode has a positive electrode layer, and optionally a positive electrode current collector.
[0019] [Positive electrode layer] The positive electrode layer may be a positive electrode mixture containing a positive electrode active material, a conductive material, and a solid electrolyte, and may optionally contain a binder, etc. The electrode mixture of the present disclosure may be a positive electrode mixture used in the positive electrode layer.
[0020] There is no particular limitation on the type of positive electrode active material, and any material that can be used as an active material for an all-solid-state battery can be used. Examples of the positive electrode active material include lithium alloys, LiCoO2, and LiNi x M 1-xO2 (wherein x satisfies 0.5≦x<1, and M is at least one element selected from the group consisting of Co, Mn, and Al), LiMnO2, Li-Mn spinel substituted with a different element, lithium titanate, lithium metal phosphate, LiCoN, Li2SiO3, Li4SiO4, transition metal oxides, TiS2, Si, SiO2, Si alloys, and lithium-storing intermetallic compounds. The Li-Mn spinel substituted with different elements is, for example, LiMn 1.5 Ni 0.5 O4, LiMn 1.5 Al 0.5 O4, LiMn 1.5 Mg 0.5 O4, LiMn 1.5 Co 0.5 O4, LiMn 1.5 Fe 0.5 O4 and LiMn 1.5 Zinc 0.5 It is O4 grade. Lithium titanate is, for example, Li4Ti5O 12 etc. Examples of lithium metal phosphates include LiFePO4, LiMnPO4, LiCoPO4, and LiNiPO4. Examples of transition metal oxides include V2O5, MoO3, etc. Examples of lithium storage intermetallic compounds include Mg2Sn, Mg2Ge, Mg2Sb, and Cu3Sb, etc. Examples of lithium alloys include Li-Au, Li-Mg, Li-Sn, Li-Si, Li-Al, Li-B, Li-C, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Ru, Li-Rh, Li-Pd, Li-Ag, Li-Cd, Li-In, Li-Sb, Li-Ir, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, Li-Tl, Li-Te, and Li-At. Examples of Si alloys include alloys with metals such as Li, and may also be alloys with at least one metal selected from the group consisting of Sn, Ge, and Al. The shape of the positive electrode active material is not particularly limited, and may be particulate. When the positive electrode active material is particulate, the positive electrode active material may be primary particles or secondary particles. A coating layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material, because this can suppress the reaction between the positive electrode active material and the solid electrolyte. Examples of Li-ion conductive oxides include LiNbO3 and Li4Ti5O 12 , and Li3PO4. The thickness of the coating layer is, for example, 0.1 nm or more, and may be 1 nm or more. On the other hand, the thickness of the coating layer is, for example, 100 nm or less, and may be 20 nm or less. The coating layer may cover, for example, 70% or more, or 90% or more of the surface of the positive electrode active material.
[0021] The conductive material may be a known material, such as a carbon material, metal particles, etc. Examples of the carbon material include acetylene black (AB), furnace black, and VGCF (Registered Trademark) , carbon nanotubes, and carbon nanofibers. Metal particles include particles of Ni, Cu, Fe, SUS, and the like. The content of the conductive material in the positive electrode layer is not particularly limited, and may be 0.4 to 6.0 mass %.
[0022] As the solid electrolyte, the same ones as those exemplified in the solid electrolyte layer can be exemplified. The content of the solid electrolyte in the positive electrode layer is not particularly limited, but may be, for example, within a range of 1 mass % to 80 mass % when the total mass of the positive electrode layer is taken as 100 mass %.
[0023] Examples of the binding agent (binder) include polyacrylonitrile, polyacrylic acid, polymethyl ester of acrylic acid, polyethyl ester of acrylic acid, polyhexyl ester of acrylic acid, polymethacrylic acid, polymethyl ester of methacrylic acid, polyethyl ester of methacrylic acid, polyhexyl ester of methacrylic acid, acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), and styrene butadiene rubber (SBR). The content of the binder in the positive electrode layer is not particularly limited.
[0024] The thickness of the positive electrode layer is not particularly limited, but may be, for example, 10 to 100 μm.
[0025] The positive electrode layer can be formed by a conventionally known method. For example, a positive electrode active material and, if necessary, other components are put into a solvent and stirred to prepare a paste for forming a positive electrode layer, and the paste for forming a positive electrode layer is applied onto one side of a support and dried to obtain a positive electrode layer. Examples of the solvent include butyl acetate, butyl butyrate, mesitylene, tetralin, heptane, and N-methyl-2-pyrrolidone (NMP). The method for applying the paste for forming a positive electrode layer onto one surface of the support is not particularly limited, and examples thereof include a doctor blade method, a metal mask printing method, an electrostatic application method, a dip coating method, a spray coating method, a roll coating method, a gravure coating method, and a screen printing method. The support can be appropriately selected from those having self-supporting properties and is not particularly limited. For example, metal foils such as Cu and Al can be used.
[0026] As another method for forming the positive electrode layer, the positive electrode layer may be formed by pressure molding a powder of a positive electrode mixture containing a positive electrode active material and other components as necessary. When the powder of the positive electrode mixture is pressure molded, a surface pressure of 1 MPa to 2000 MPa and a linear pressure of 1 ton / cm to 100 ton / cm are usually applied. The method of applying pressure is not particularly limited, but examples thereof include a method of applying pressure using a plate press, a roll press, or the like.
[0027] [Positive electrode current collector] The positive electrode current collector may be a known metal that can be used as a current collector for an all-solid-state battery. Examples of such metals include metal materials containing one or more elements selected from the group consisting of Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Co, Cr, Zn, Ge, and In. Examples of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. The shape of the positive electrode current collector is not particularly limited, and may be in various shapes such as a foil shape, a mesh shape, etc. The thickness of the positive electrode current collector varies depending on the shape, but may be, for example, in the range of 1 μm to 50 μm, or in the range of 5 μm to 20 μm.
[0028] [Negative electrode] The negative electrode has a negative electrode layer, and optionally has a negative electrode current collector.
[0029] [Negative electrode layer] The negative electrode layer may be a negative electrode mixture containing at least a negative electrode active material, a conductive material, and a solid electrolyte, and may optionally contain a binder, etc. The electrode mixture of the present disclosure may be a negative electrode mixture used in the negative electrode layer. The negative electrode active materials include graphite, mesocarbon microbeads (MCMB), highly oriented pyrolytic graphite (HOPG), hard carbon, soft carbon, lithium, lithium alloys, Si, Si alloys, and Li4Ti5O 12As the lithium alloy and the Si alloy, the same ones as those exemplified in the positive electrode active material can be used. The shape of the negative electrode active material is not particularly limited, and examples thereof include a particulate shape, a plate shape, etc. When the negative electrode active material is particulate, the negative electrode active material may be primary particles or secondary particles. The conductive material and binder used in the negative electrode layer may be the same as those exemplified in the positive electrode layer. The solid electrolyte used in the negative electrode layer may be the same as those exemplified in the solid electrolyte layer. The thickness of the negative electrode layer is not particularly limited, but may be, for example, 10 to 100 μm. The content of the negative electrode active material in the negative electrode layer is not particularly limited, and may be, for example, 20% by mass to 90% by mass. The method for forming the negative electrode layer includes a method of applying a paste for forming the negative electrode layer containing a negative electrode active material onto a support and drying the paste, etc. The support may be the same as those exemplified for the positive electrode layer.
[0030] [Negative electrode current collector] The material of the negative electrode current collector may be a material that does not alloy with Li, and examples of such materials include SUS, copper, and nickel. Examples of the shape of the negative electrode current collector include foil and plate. The planar shape of the negative electrode current collector is not particularly limited, and examples of such shapes include a circle, an ellipse, a rectangle, and any polygonal shape. The thickness of the negative electrode current collector varies depending on the shape, and may be, for example, within a range of 1 μm to 50 μm, or within a range of 5 μm to 20 μm.
[0031] [Solid electrolyte layer] The solid electrolyte layer includes at least a solid electrolyte. As the solid electrolyte contained in the solid electrolyte layer, a known solid electrolyte that can be used in an all-solid-state battery can be appropriately used, and examples of such solid electrolytes include inorganic solid electrolytes such as sulfide-based solid electrolytes, oxide-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, and nitride-based solid electrolytes. The sulfide-based solid electrolyte may contain sulfur (S) as a main component of the anion element. The oxide-based solid electrolyte may contain oxygen (O) as a main component of the anion element. The hydride-based solid electrolyte may contain hydrogen (H) as a main component of the anion element. The halide-based solid electrolyte may contain halogen (X) as a main component of the anion element. The nitride-based solid electrolyte may contain nitrogen (N) as a main component of the anion element.
[0032] The sulfide-based solid electrolyte may be a sulfide glass, a crystallized sulfide glass (glass ceramics), or a crystalline material obtained by subjecting a raw material composition to a solid-phase reaction treatment. The crystalline state of the sulfide-based solid electrolyte can be confirmed, for example, by subjecting the sulfide-based solid electrolyte to powder X-ray diffraction measurement using CuKα radiation.
[0033] The sulfide glass can be obtained by subjecting a raw material composition (e.g., a mixture of Li2S and P2S5) to an amorphous process, such as mechanical milling.
[0034] Glass ceramics can be obtained, for example, by heat treating a sulfide glass. The heat treatment temperature may be any temperature higher than the crystallization temperature (Tc) of the sulfide glass observed by thermal analysis, and is usually 195° C. or higher. On the other hand, there is no particular upper limit to the heat treatment temperature. The crystallization temperature (Tc) of the sulfide glass can be measured by differential thermal analysis (DTA). The heat treatment time is not particularly limited as long as the desired crystallinity of the glass ceramic is obtained, but is, for example, within the range of 1 minute to 24 hours, and particularly within the range of 1 minute to 10 hours. The method of heat treatment is not particularly limited, but may be, for example, a method using a baking furnace.
[0035] Examples of oxide-based solid electrolytes include solid electrolytes containing Li, Y (Y is at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W, and S), and O. Specific examples of oxide-based solid electrolytes include Li7La3Zr2O 12 , Li 7-x La3(Zr 2-x Nb x )O 12 (0≦x≦2), Li5La3Nb2O 12 perovskite-type solid electrolytes such as (Li,La)TiO3, (Li,La)NbO3, (Li,Sr)(Ta,Zr)O3; Nasicon-type solid electrolytes such as Li(Al,Ti)(PO4)3 and Li(Al,Ga)(PO4)3; Li-PO-based solid electrolytes such as Li3PO4 and LIPON (a compound in which some of the O in Li3PO4 is replaced with N); and Li-BO-based solid electrolytes such as Li3BO3 and a compound in which some of the O in Li3BO3 is replaced with C. In the present disclosure, the notation "(A,B,C)" in a chemical formula means "at least one selected from the group consisting of A, B, and C."
[0036] The hydride-based solid electrolyte has, for example, Li and a complex anion containing hydrogen. The complex anion is, for example, (BH4) - , (NH2) - , (AlH4) - , and (AlH6) 3- etc.
[0037] The halide-based solid electrolyte is, for example, represented by the following composition formula (1). Li α M β X γ ...Equation (1) In the composition formula (1), α, β, and γ are each independently a value greater than 0. M includes at least one element selected from the group consisting of metal elements and metalloid elements other than Li. X includes at least one element selected from the group consisting of F, Cl, Br, and I. In the present disclosure, the "metalloid elements" are B, Si, Ge, As, Sb, and Te. The "metal elements" are all elements in Groups 1 to 12 of the periodic table except for hydrogen, and all elements in Groups 13 to 16 of the periodic table except for B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se. In other words, the "metalloid elements" or "metal elements" are a group of elements that can become cations when forming an inorganic compound with a halogen element. More specifically, examples of halide-based solid electrolytes include Li3YX6, Li2MgX4, Li2FeX4, LiAlX4, LiGaX4, LiInX4, Li3AlX6, Li3GaX6, and Li3InX6, where X is at least one selected from the group consisting of F, Cl, Br, and I.
[0038] An example of the nitride-based solid electrolyte is Li3N.
[0039] The solid electrolyte may be in the form of particles from the viewpoint of ease of handling. The average particle size of the solid electrolyte particles is not particularly limited, but may be, for example, 10 nm or more, and may be 100 nm or more, while the average particle size of the solid electrolyte particles is, for example, 25 μm or less, and may be 10 μm or less.
[0040] In this disclosure, the average particle size of particles is the volume-based median diameter (D50) value measured by laser diffraction / scattering particle size distribution measurement, unless otherwise specified. In this disclosure, the median diameter (D50) is the diameter (volume average diameter) at which the cumulative volume of particles is half (50%) of the total volume when the particles are arranged in order from the smallest particle size.
[0041] The solid electrolyte may be used alone or in combination of two or more kinds. When two or more kinds of solid electrolytes are used, the two or more kinds of solid electrolytes may be mixed, or two or more layers of the solid electrolyte may be formed to form a multilayer structure. The proportion of the solid electrolyte in the solid electrolyte layer is not particularly limited, but is, for example, 50% by mass or more, may be in the range of 60% by mass or more and 100% by mass or less, may be in the range of 70% by mass or more and 100% by mass or less, or may be 100% by mass.
[0042] The solid electrolyte layer may contain a binder from the viewpoint of expressing plasticity, etc. Examples of such binders include the materials exemplified as the binders used in the positive electrode layer. However, in order to facilitate high output, the binder may be contained in the solid electrolyte layer in an amount of 5 mass% or less from the viewpoint of preventing excessive aggregation of the solid electrolyte and enabling the formation of a solid electrolyte layer having a uniformly dispersed solid electrolyte.
[0043] The thickness of the solid electrolyte layer is not particularly limited, and is usually 0.1 μm or more and 1 mm or less. The method for forming the solid electrolyte layer includes a method of applying a paste for forming a solid electrolyte layer containing a solid electrolyte onto a support and drying it, and a method of pressurizing a powder of a solid electrolyte material containing a solid electrolyte. The support may be the same as those exemplified for the positive electrode layer. When pressurizing the powder of the solid electrolyte material, a press pressure of about 1 MPa or more and 2000 MPa or less is usually applied. The method of applying pressure is not particularly limited, but may be any of the pressure applying methods exemplified in the formation of the positive electrode layer.
[0044] The all-solid-state battery may, as necessary, include an exterior body that houses a laminate including a positive electrode current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode current collector in this order, and a restraining member and the like. The material of the exterior body is not particularly limited as long as it is stable with respect to the solid electrolyte, and examples of the material include polypropylene, polyethylene, and resins such as acrylic resin. The restraining member may be any known member usable as a battery restraining member as long as it can apply a restraining pressure in the stacking direction to the laminate. For example, a restraining member having plate-shaped parts that sandwich both surfaces of the laminate, a rod-shaped part that connects the two plate-shaped parts, and an adjustment part that is connected to the rod-shaped part and adjusts the restraining pressure by a screw structure or the like can be used. The adjustment part can apply a desired restraining pressure to the laminate. The restraining pressure is not particularly limited, but may be, for example, 0.1 MPa or more, 1 MPa or more, or 5 MPa or more. By increasing the restraining pressure, there is an advantage that it is easier to improve the contact between the layers. On the other hand, the restraining pressure may be, for example, 100 MPa or less, 50 MPa or less, or 20 MPa or less. If the restraining pressure is too high, the restraining member is required to have high rigidity, and the restraining member may become large.
[0045] The all-solid-state battery may have only one of the laminates described above, or may be formed by laminating a plurality of the laminates. The all-solid-state battery may be an all-solid-state lithium-ion secondary battery or the like. Examples of the shape of the all-solid-state battery include a coin type, a laminate type, a cylindrical type, and a square type. The use of the all-solid-state battery is not particularly limited, but examples thereof include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, the all-solid-state battery may be used as a driving power source for hybrid electric vehicles, plug-in hybrid electric vehicles, or electric vehicles. The all-solid-state battery of the present disclosure may also be used as a power source for moving objects other than vehicles (e.g., railways, ships, and aircraft), and may also be used as a power source for electrical products such as information processing devices.
[0046] In the method for producing an all-solid-state battery of the present disclosure, for example, a solid electrolyte layer is formed by first applying a paste for forming a solid electrolyte layer to a support and drying it. Then, a paste for forming a positive electrode layer containing a positive electrode active material is applied on one side of the solid electrolyte layer and dried to obtain a positive electrode layer. Thereafter, the support is peeled off from the solid electrolyte layer, and a paste for forming an anode layer is applied on the other side of the solid electrolyte layer and dried to form a negative electrode layer. If necessary, a positive electrode current collector may be attached to the side of the positive electrode layer opposite the solid electrolyte layer, and a negative electrode current collector may be attached to the side of the negative electrode layer opposite the solid electrolyte layer to form an all-solid-state battery. EXAMPLES
[0047] Example 1 [Preparation of positive electrode] Positive electrode active material (LiNi 0.8 Co 0.15 Al 0.05 O2, average particle size 10 μm), sulfide-based solid electrolyte (10LiI 15LiBr 75 (0.75Li2S 0.25P2S5) (mol%), conductive material (VGCF (Registered Trademark) -H, strength ratio D / G0.05, specific surface area 13m 2 / g) and a binder (SBR) were weighed out so that the mass ratio of the positive electrode active material:sulfide-based solid electrolyte:conductive material:binder was 69.3:30.0:0.5:0.2, and mixed with a dispersion medium (diisobutyl ketone). The obtained mixture was dispersed with an ultrasonic homogenizer (UH-50, manufactured by SMT Co., Ltd.) to obtain a slurry for forming a positive electrode layer. The obtained slurry for forming a positive electrode layer was applied to an Al foil (thickness 15 μm) by a blade coating method using an applicator, and dried at 100 ° C. for 30 minutes to obtain a positive electrode having a positive electrode layer and an Al foil. The thickness of the positive electrode layer was 100 μm. The positive electrode layer is the electrode mixture of the present disclosure. Table 1 shows the results of calculating the conductive load parameters of the conductive material and the measurement of the contact interface length between the conductive material and the solid electrolyte. FIG. 1 is a diagram showing the results of Raman spectrum measurement of the conductive material used in Example 1.
[0048] [Preparation of negative electrode] The negative electrode active material (Si particles, average particle size 0.5 μm), sulfide-based solid electrolyte (10LiI 15LiBr 75 (0.75Li2S 0.25P2S5) (mol%), average particle size 0.5 μm), and conductive material (VGCF (Registered Trademark) -H) and a binder (SBR) were weighed out so that the mass ratio (mass%) of the negative electrode active material: sulfide-based solid electrolyte: conductive material: binder was 47.0: 44.6: 7.0: 1.4, and mixed with a dispersion medium (diisobutyl ketone). The obtained mixture was dispersed with an ultrasonic homogenizer (UH-50, manufactured by SMT Co., Ltd.) to obtain a slurry for forming a negative electrode layer. The obtained slurry for forming a negative electrode layer was applied to a negative electrode current collector (Ni foil, thickness 22 μm) by a blade coating method using an applicator, and dried at 100 ° C for 30 minutes to obtain a negative electrode having a negative electrode current collector and a negative electrode layer. The thickness of the negative electrode layer was 60 μm.
[0049] [Preparation of solid electrolyte layer] A sulfide-based solid electrolyte (10LiI 15LiBr 75 (0.75Li2S 0.25P2S5) (mol%), average particle size 2.0 μm) and a binder (SBR) were weighed out so that the mass ratio of sulfide-based solid electrolyte:binder was 99.6:0.4, and mixed with a dispersion medium (diisobutyl ketone). The mixture was dispersed with an ultrasonic homogenizer (UH-50, manufactured by SMT Co., Ltd.) to obtain a slurry for forming a solid electrolyte layer. The obtained slurry for forming a solid electrolyte layer was applied to an Al foil (thickness 15 μm) by a blade coat method using an applicator, and dried at 100 °C for 30 minutes to obtain a solid electrolyte layer with an Al foil. The thickness of the solid electrolyte layer was 30 μm. In Examples 1 to 5, the sulfide-based solid electrolyte was heated using a hot plate in an atmosphere with a dew point of −70° C. and 20% oxygen to form a lithium sulfate coating.
[0050] [Preparation of all-solid-state lithium-ion secondary batteries] A solid electrolyte layer was placed on the negative electrode layer of the negative electrode, the Al foil was peeled off from the solid electrolyte layer, and a positive electrode was laminated on the solid electrolyte layer so that the positive electrode layer was in contact with the solid electrolyte layer, and pressed at 130° C. and 5 ton / cm. This produced an all-solid-state lithium ion secondary battery for evaluation, which is an evaluation cell having a positive electrode, a solid electrolyte layer, and a negative electrode in this order.
[0051] Example 2 In the above [Preparation of Positive Electrode], the positive electrode active material:sulfide-based solid electrolyte:conductive material:binder=68.3:30.0:1.5:0.2 were weighed out, and a positive electrode and an all-solid-state lithium ion secondary battery were obtained in the same manner as in Example 1. The conductive load parameters of the conductive material and the contact interface length between the conductive material and the solid electrolyte are shown in Table 1.
[0052] Example 3 In the above [Preparation of Positive Electrode], the positive electrode active material:sulfide-based solid electrolyte:conductive material:binder=67.8:30.0:2.0:0.2, except for that, a positive electrode and an all-solid-state lithium ion secondary battery were obtained in the same manner as in Example 1. The conductive load parameters of the conductive material and the contact interface length between the conductive material and the solid electrolyte are shown in Table 1.
[0053] Example 4 In the above [Preparation of Positive Electrode], the positive electrode active material:sulfide-based solid electrolyte:conductive material:binder=66.8:30.0:3.0:0.2 were weighed out, and other than that, a positive electrode and an all-solid-state lithium ion secondary battery were obtained in the same manner as in Example 1. The conductive load parameters of the conductive material and the contact interface length between the conductive material and the solid electrolyte are shown in Table 1.
[0054] Example 5 In the above [Preparation of the positive electrode], VGCF was used as the conductive material. (Registered Trademark) -H (strength ratio D / G0.05, specific surface area 13m 2 / g) and AB (intensity ratio D / G 0.9, specific surface area 120 m 2 / g) and positive electrode active material: sulfide-based solid electrolyte: conductive material VGCF (Registered Trademark)Except for the weighting of -H:conductive material AB:binder=67.5:30.0:1.8:0.5:0.2, a positive electrode and an all-solid-state lithium ion secondary battery were obtained in the same manner as in Example 1. The conductive load parameters of the conductive material and the contact interface length between the conductive material and the solid electrolyte are shown in Table 1.
[0055] Comparative Example 1 In the above [Preparation of Positive Electrode], the positive electrode active material: sulfide-based solid electrolyte: conductive material: binder = 69.4: 30.0: 0.4: 0.2, except for that, a positive electrode and an all-solid-state lithium ion secondary battery were obtained in the same manner as in Example 1. The conductive load parameters of the conductive material and the contact interface length between the conductive material and the solid electrolyte are shown in Table 1.
[0056] Comparative Example 2 In the above [Preparation of Positive Electrode], the positive electrode active material: sulfide-based solid electrolyte: conductive material: binder = 64.8: 30.0: 6.0 (5.95: 0.2) were weighed out, and a positive electrode and an all-solid-state lithium ion secondary battery were obtained in the same manner as in Example 1. The conductive load parameters of the conductive material and the contact interface length between the conductive material and the solid electrolyte are shown in Table 1.
[0057] [Charge / discharge test] Using the evaluation cells of Examples 1 to 5 and Comparative Examples 1 and 2, charge / discharge tests were carried out under the following conditions. Each evaluation cell was bound to a fixed size at a binding pressure of 5 MPa and charged at a constant current-constant voltage (CC-CV) at 0.461 mA to 2.7 V. Then, CC-CV discharge was performed at 0.461 mA to 3.0 V. The all-solid-state lithium-ion secondary battery was then charged again. This charge was designated as the first (initial) charge. Then, the first (initial) discharge was performed, and the discharge capacity (mAh / g) was calculated. The calculated discharge capacity is shown in Table 1. Then, the charge / discharge cycle was performed at 2C up to 300 cycles.
[0058] [Strength ratio B / A] XPS was performed on each evaluation cell, and the intensity ratio B / A of the peak intensity B near 162 eV to the peak intensity A near 159 to 160 eV in the sulfur S2p spectrum of the solid electrolyte obtained was calculated. The calculated intensity ratios B / A are shown in Table 1. FIG. 2 is a diagram showing the measurement results of the sulfur S2p spectrum of the solid electrolyte used in Example 1.
[0059] [Resistance rating] The internal resistance of each evaluation cell was evaluated by the impedance method. Specifically, after the initial charge and discharge, each evaluation cell was adjusted to SOC 20%, and the circular hole component of the impedance was calculated, which was used as the initial resistance. The calculation results of the initial resistance are shown in Table 1. The resistance after 300 cycles was calculated in the same manner, and the resistance increase rate after 300 cycles was calculated by dividing the resistance after 300 cycles by the initial resistance. The calculation results of the resistance increase rate after 300 cycles are shown in Table 1.
[0060] [Table 1]
[0061] [Evaluation Results] As shown in Table 1, Examples 1 to 5 have lower initial resistance and higher discharge capacity than Comparative Example 1. Furthermore, Examples 1 to 5 have lower resistance increase rates after 300 cycles than Comparative Example 2. Therefore, it was demonstrated that Examples 1 to 5 have an excellent balance between initial resistance, discharge capacity, and resistance increase rate.
Claims
1. An electrode mixture for an all-solid-state battery, The battery includes an active material, a solid electrolyte, and a conductive material, In the Raman spectrum measurement of the conductive material, -1 Intensity G of the peak at 1350 cm -1 The intensity ratio D / G of the peak intensity D of the conductive material is multiplied by the content W (mass%) of the conductive material to obtain the specific surface area Si (m 2 / g) and multiplying the result by 100, the conductive load parameter of the conductive material is greater than 0.16 and less than or equal to 0.
57.
2. An all-solid-state battery, The all-solid-state battery comprises the electrode mixture according to claim 1, An all-solid-state battery in which an intensity ratio B / A of a peak intensity B near 162 eV to a peak intensity A near 159 to 160 eV in a sulfur S2p spectrum of the solid electrolyte obtained by X-ray photoelectron spectroscopy (XPS) after initial charging and discharging of the all-solid-state battery is greater than 0.39 and less than 0.51.
Citation Information
Patent Citations
Positive electrode mixture
JP2013258080A
Negative electrode
JP2020119774A
Manufacturing method of positive electrode slurry, manufacturing method of positive electrode, manufacturing method of all-solid battery, positive electrode, and all-solid battery
JP2020145034A
All-solid battery
JP2021072259A
Novel conductive material, electrode including said conductive material, secondary battery including said electrode, and method for producing said conductive material
JP2021508156A